2017
DOI: 10.18632/oncotarget.18514
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like growth factor-1 is a negative modulator of glucagon secretion

Abstract: Glucagon secretion involves a combination of paracrine, autocrine, hormonal, and autonomic neural mechanisms. Type 2 diabetes often presents impaired glucagon suppression by insulin and glucose. Insulin-like growth factor-I (IGF-1) has elevated homology with insulin, and regulates pancreatic β-cells insulin secretion. Insulin and IGF-1 receptors share considerable structure homology and function. We hypothesized the existence of a mechanism linking the inhibition of α-cells glucagon secretion to IGF-1. Herein,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 58 publications
1
13
0
Order By: Relevance
“…The first step of β-cell failure and IGT occurs when postprandial GLP-1 levels begin to decline. 39 Prospective studies in human and non-human primates have conclusively demonstrated that insulin resistance and hyperinsulinemia precede the development of IGT and that IGT represents the forerunner of T2DM.…”
Section: What Is Diabetes Mellitus?mentioning
confidence: 99%
See 2 more Smart Citations
“…The first step of β-cell failure and IGT occurs when postprandial GLP-1 levels begin to decline. 39 Prospective studies in human and non-human primates have conclusively demonstrated that insulin resistance and hyperinsulinemia precede the development of IGT and that IGT represents the forerunner of T2DM.…”
Section: What Is Diabetes Mellitus?mentioning
confidence: 99%
“…GLP‐1 is secreted from L cells in the intestinal ileum. GLP‐1 increases glucose transporter 2 expression in pancreatic β‐cells which increases β‐cell sensitivity to glucose for increased insulin secretion, while also restricting glucagon release from the α‐cells and reducing hepatic glucose production. The first step of β‐cell failure and IGT occurs when postprandial GLP‐1 levels begin to decline .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been recently shown that Insulin-like growth factor-1 (IGF-1) may play a regulatory role in glucagon secretion in Caucasian subjects without diabetes [28] . The impaired glucagon suppression index seen in our abnormal glucose tolerance group thus could be mediated by an effect of altered IGF-1 concentrations in the alpha cells.…”
Section: Discussionmentioning
confidence: 99%
“…This finding suggests that macrophage-derived IGF-1 is important in limiting beta-cell functional damage post-STZ. While it was beyond the scope of this study to determine the cell-specific actions of macrophage-derived IGF-1, effects on insulin secretion and glucose homeostasis may be due to direct effects of IGF-1 on beta cells (Kulkarni et al, 2002, Dheen et al, 1996, or indirect effects on alpha-cell glucagon secretion (Mancuso et al, 2017), or on other islet cell types to limit tissue inflammation (Han et al, 2016).…”
Section: Limitations Of the Studymentioning
confidence: 99%